The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1152/japplphysiol.00014.2003
|View full text |Cite
|
Sign up to set email alerts
|

Acute molecular responses of skeletal muscle to resistance exercise in able-bodied and spinal cord-injured subjects

Abstract: . Acute molecular responses of skeletal muscle to resistance exercise in ablebodied and spinal cord-injured subjects. J Appl Physiol 94: 2255-2262. First published February 28, 2003 10.1152/japplphysiol.00014.2003.-Spinal cord injury (SCI) results in muscle atrophy, which contributes to a number of health problems, such as cardiovascular deconditioning, metabolic derangement, and osteoporosis. Electromyostimulation (EMS) holds the promise of ameliorating SCI-related muscle atrophy and, therefore, improving ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
87
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 45 publications
12
87
1
6
Order By: Relevance
“…The 15% increase in quadriceps CSA confirms previous studies that showed muscle increase in chronic spinal cord-injured patients using NMES in other modalities of therapy [3,19]. Two studies suggest NMES does not reverse muscle atrophy in chronic spinal cord-injured patients [1,16] but can promote moderate increases after muscle contractions against some external load [20,21].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The 15% increase in quadriceps CSA confirms previous studies that showed muscle increase in chronic spinal cord-injured patients using NMES in other modalities of therapy [3,19]. Two studies suggest NMES does not reverse muscle atrophy in chronic spinal cord-injured patients [1,16] but can promote moderate increases after muscle contractions against some external load [20,21].…”
Section: Discussionsupporting
confidence: 82%
“…The inability to find increases in muscle CSA after gait training without NMES was possibly the result of insufficient mechanical load imposed on paralyzed muscles (reduction of 30%-50% of body weight during gait) associated with severity of the spinal cord lesion (complete and extensive lesions). Although the data at the beginning of gait training with and without NMES tended to be different, it has been reported that muscles of subjects with chronic spinal cord injuries can improve after exercise [3,14,19,22]. This fact was observed in subjects with low CSA values in the gait group, who also benefited from the training.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This provides a possible explanation for muscle atrophy in SCI rats because SCI hinders the rat 0 s movements and leads to diminished locomotor activity. 15,16 A possible limitation of this is that, because of technical problems, ferritin levels were not determined. Such an analysis would be extremely important because ferritin is an endothelial reticulum protein responsible for storing iron, and there is a relationship between serum ferritin levels and the amount of iron stored.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with CTRL1, the SCI1 (1 day after SCI) and the SHAM1 group showed significantly reduced levels of plasma iron (F (2,15) ¼ 12.008, P ¼ 0.00077; ANOVA) and transferrin (F (2,15) ¼ 25.688, P ¼ 0.00001; ANOVA) ( Figure 1a).…”
Section: Experiment: Acute Sci (Sci1)mentioning
confidence: 99%